2003
DOI: 10.1046/j.1399-6576.2003.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for mast cell tryptase and serum IgE antibodies in 18 patients with anaphylactic shock during general anaesthesia

Abstract: Fifteen out of 18 sera tested positive for MCT and/or specific IgE against neuromuscular blocking drugs (NMBDs). Ten of the 18 patients experienced an IgE-mediated anaphylactic reaction to NMBDs during anaesthesia, verified by detection of specific IgE and elevated levels of MCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 28 publications
1
42
0
3
Order By: Relevance
“…Additionally, after initiating a cardiopulmonary bypass which stabilized patient hemodynamic collapse, we obtained a blood sample to test for mast cell tryptase. This approach is in agreement with current practice of diagnosing anaphylaxis during the perioperative period [3,4]. The test came positive, confirming the occurrence of severe anaphylactic reaction.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, after initiating a cardiopulmonary bypass which stabilized patient hemodynamic collapse, we obtained a blood sample to test for mast cell tryptase. This approach is in agreement with current practice of diagnosing anaphylaxis during the perioperative period [3,4]. The test came positive, confirming the occurrence of severe anaphylactic reaction.…”
supporting
confidence: 88%
“…Indeed, several medications used to induce and maintain general anaesthesia have been described as strong allergens. The most common are non-depolarizing muscle relaxants and antibiotics [2,3]. Dr. Kounis and colleagues have suggested that salbutamol could aggravate hemodynamic collapse; this is an excellent point as this beta mimetic certainly causes tachycardia, which can worsen hemodynamic compromise in patients suffering from HOCM, Additionally, they suggested that preservatives present in ampoules of epinephrine (for example, sulphites) may also contribute to allergic reactions.…”
mentioning
confidence: 99%
“…Mast cell tryptase also circulates in the body, and although serum tryptase levels are quite low in healthy individuals (Ͻ1 ϫ 10 Ϫ10 M), they can be 10 -100-fold higher in patients undergoing anaphylactic reactions (21). Although low concentrations of tryptase (5.2 ϫ 10 Ϫ11 M) did not activate chemerin, higher concentrations (5.2 ϫ 10 Ϫ9 M) served as a potent activator (TABLE ONE).…”
Section: Serinementioning
confidence: 99%
“…It is practically impossible to perform a skin test on every medication administered during anaesthesia for every patient. 9,10 The diagnosis of anaphylactic reactions is difficult to make during the induction of anaesthesia when various types of medication are used simultaneously. Therefore, it is mandatory to make a prompt diagnosis, and to provide a proper treatment for its occurrence.…”
Section: Resultsmentioning
confidence: 99%